Development of α‐Gal–Antibody Conjugates to Increase Immune Response by Recruiting Natural Antibodies. Issue 14 (8th March 2019) - Sianturi, Julinton; Manabe, Yoshiyuki; Li, Hao‐Sheng; Chiu, Li‐Ting; Chang, Tsung‐Che; Tokunaga, Kento; Kabayama, Kazuya; Tanemura, Masahiro; Takamatsu, Shinji; Miyoshi, Eiji; Hung, Shang‐Cheng; Fukase, Koichi
Abstract: Cancer treatment with antibodies (Abs) is one of the most successful therapeutic strategies for obtaining high selectivity. In this study, α‐gal–Ab conjugates were developed that dramatically increased cellular cytotoxicity by recruiting natural Abs through the interaction between α‐gal and anti‐gal Abs. The potency of the α‐gal–Ab conjugates depended on the amount of α‐gal conjugated to the antibody: the larger the amount of α‐gal introduced, the higher the level of cytotoxicity observed. The conjugation of antibodies with an α‐gal dendrimer allowed the introduction of large amounts of α‐gal to the Ab, without loss of affinity for the target cell. The method described here will enable the re‐development of Abs to improve their potency. Abstract : α‐Gal–antibody (Ab) conjugates have been developed that can dramatically increase cellular cytotoxicity by recruiting natural Abs through the interaction between α‐gal and anti‐gal Abs. The potency of the α‐gal–Ab conjugates increased with the amount of α‐gal conjugated to the Ab. The method developed here will enable the re‐development of Abs to improve their potency.